Zinc silicate mineral-coated scaffold improved in vitro osteogenic differentiation of equine adipose-derived mesenchymal stem cells. (June 2019) - Bageshlooyafshar, Behnaz; Vakilian, Saeid; Kehtari, Mousa; Eslami-Arshaghi, Tarlan; Rafeie, Farjad; Ramezanifard, Rouhallah; Rahchamani, Reza; Mohammadi-Sangcheshmeh, Abdollah; Mostafaloo, Yousef; Seyedjafari, Ehsan
Abstract: In current study we aimed to coat the PLLA scaffold with zinc (Zn) silicate mineral nanoparticles. Then, using equine adipose-derived stem cells (ASCs) we intended to compare the osteogenic induction potency of Zn silicate mineral-coated PLLA scaffold with uncoated PLLA scaffold and tissue culture plastic (TCPS). Adipose tissues were collected from 3 horses, and isolation of ASCs was achieved by enzymatic digestion. PLLA scaffold was successfully prepared using a phase separation method and coated with Zn silicate mineral nanoparticles. The coating efficiency was then characterized by scanning electron microscopy and further evaluated with the application of fourier transform infrared microscopic imaging. Viability and growth characteristics of ASCs on TCPS, uncoated and coated PLAA scaffolds were investigated by MTT assay. Alizarin Red staining was performed for determination of calcium deposition following the osteogenic induction. Furthermore, other common osteogenic markers such as alkaline phosphatase ( ALP ) activity, calcium content, as well as osteogenic ( Runx2, ALP, osteonectin, and collagen I ) marker genes were also evaluated. Our data showed that Zn silicate mineral nanoparticles was coated successfully on PLLA scaffold and such scaffold had no detrimental effect on cell growth rate as indicated by MTT assay. Moreover, ASCs that differentiated on Zn silicate mineral-coated PLLA scaffold indicated higher ALP activity, more calcium content, and higher expression of bone-related genes than that on uncoated PLLA scaffold and TCPS. Adequate proliferation rate and higher expression of osteogenic markers of stem cells, provides this scaffold as a suitable substrate to support proliferation and differentiation of ASCs in equine. Highlights: Zn silicate mineral nanoparticles was coated successfully on PLLA scaffold. The coated scaffold had no detrimental effect on cell growth rate as indicated by MTT assay. The osteogenic differentiated ASCs on Zn silicate mineral-coated PLLA scaffold indicated higher ALP activity. The osteogenic differentiated ASCs indicated more calcium content, and higher expression of bone-related genes.